Reactive solid polymer electrolyte as well as preparation method and application thereof

By connecting polyethylene polyethylene side chains on the surface of bacterial cellulose and distributed modified bacterial cellulose and lithium salt on polyethylene ethylene basis, the electrolyte of reactive solid -state polymer is prepared The problem of poor rates and mechanical properties realizes higher conductivity and better mechanical properties, and significantly improves the cycle stability of lithium batteries.

CN119361812AActive Publication Date: 2025-01-24SUN YAT SEN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411249124.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2025-01-24
Estimated Expiration
2044-09-06

AI Technical Summary

Technical Problem

The existing PEO solid-state polymer electrolytes have problems such as low ionic conductivity, poor mechanical properties and unstable electrolyte/electrode interface.

Method used

A reactive molecular brushes are formed by the polyethylene cepteriimazole side chain of the bacterial cellulose surface. Electrolyte.

Benefits of technology

It improves the ion conductivity and mechanical properties of solid electrolytes, inhibits the growth of lithium branches, and forms a stable electrolyte/electrode interface during the charging and discharge process, significantly improved the cycle stability of the lithium battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361812A_ABST
    Figure CN119361812A_ABST
Patent Text Reader

Abstract

The invention discloses a reactive solid polymer electrolyte and a preparation method and application thereof, and belongs to the technical field of electrolytes. The reactive solid polymer electrolyte provided by the invention comprises a polyoxyethylene base, and modified bacterial cellulose and lithium salt which are dispersed on the polyoxyethylene base, wherein the modified bacterial cellulose is a reactive molecular brush formed by grafting an alkylated polyvinyl imidazole side chain on the surface of the bacterial cellulose; the mass ratio of the modified bacterial cellulose is 5%-20%. Through molecular structure design of bacterial cellulose, rapid transmission of lithium ions can be promoted, the ionic conductivity of the electrolyte can be improved, a rigid cellulose skeleton can endow the solid polymer electrolyte with excellent mechanical properties, and meanwhile, a stable electrolyte / electrode interface can be formed; therefore, the cycling stability of the lithium battery is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of electrolyte technology, and in particular relates to a reactive solid polymer electrolyte and a preparation method and application thereof. Background Art

[0002] Solid electrolytes replace the electrolyte and separator in traditional lithium-ion batteries, and play the functional role of conducting ions and connecting the positive and negative electrodes. Solid electrolytes are mainly divided into three categories: solid polymer electrolytes, inorganic solid electrolytes, and organic-inorganic composite solid electrolytes. In contrast, solid polymer electrolytes are widely used because of their good flexibility, processability and thermal stability. Among them, polyethylene oxide (PEO) is a widely used one. However, PEO solid polymer electrolytes generally have problems such as low ionic conductivity, poor mechanical properties, and unstable electrolyte / electrode interface. Therefore, the need to develop solid polymer electrolytes with excellent comprehensive performance is a technical problem that needs to be solved urgently.

[0003] At present, fillers are usually added to improve the performance of PEO solid polymer electrolytes. The prior art with application publication number CN113471531 A discloses a polymer solid electrolyte, which comprises a plant cellulose aerogel matrix, a comb-shaped PEO-based polymer and a lithium salt, and the comb-shaped PEO-based polymer and the lithium salt are filled in the pores of the plant cellulose aerogel matrix.

[0004] However, the above-mentioned PEO solid polymer electrolyte has the following problems: first, while improving the conductivity, it will lead to a decrease in the mechanical strength of the polymer electrolyte, causing a safety hazard; second, it is easy to cause instability in the electrolyte / electrode interface, resulting in a shorter battery life. Summary of the invention

[0005] The present application discloses a reactive solid polymer electrolyte and a preparation method and application thereof, aiming to solve the technical problems of low ion conductivity, poor mechanical properties and unstable electrolyte / electrode interface of existing PEO solid polymer electrolytes.

[0006] In order to achieve the above purpose, the technical solution of this application is:

[0007] The first aspect of the present application provides a reactive solid polymer electrolyte, comprising a polyethylene oxide substrate and modified bacterial cellulose and a lithium salt dispersed on the polyethylene oxide substrate;

[0008] Wherein, the modified bacterial cellulose is a reactive molecular brush formed by grafting alkylated polyvinyl imidazole side chains on the surface of bacterial cellulose;

[0009] The mass ratio of the modified bacterial cellulose to the polyethylene oxide substrate is 5%-20%.

[0010] In combination with the first aspect, preferably, the lithium salt is one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide and lithium difluorooxalatoborate.

[0011] The second aspect of the present application provides a method for preparing the reactive solid polymer electrolyte according to the first aspect, the method comprising:

[0012] After dispersing bacterial cellulose in N,N-dimethylformamide, adding 4-dimethylaminopyridine and triethylamine to react, then adding 2-bromoisobutyryl bromide to react, separating and collecting to obtain an intermediate product I;

[0013] The intermediate product I, 1-vinylimidazole, a ligand, a catalyst, and a reducing agent are subjected to polymerization reaction in N,N-dimethylformamide, and then separated and collected to obtain an intermediate product II;

[0014] The intermediate product II is subjected to an alkylation reaction with n-butyl iodide to obtain the modified bacterial cellulose;

[0015] The modified bacterial cellulose, polyethylene oxide and lithium salt are mixed, volatilized to form a film and solidified to obtain the reactive solid polymer electrolyte.

[0016] In combination with the second aspect, preferably, the ligand is one or a combination of N,N,N',N",N"-pentamethyldiethylenetriamine, 2,2-bipyridine and tris(2-picolylmethyl)amine.

[0017] In combination with the second aspect, preferably, the catalyst is one or more of cupric bromide, cupric chloride, cuprous bromide and cuprous chloride.

[0018] In combination with the second aspect, preferably, the reducing agent is one or more of ascorbic acid, stannous isooctanoate, and thiourea dioxide.

[0019] In combination with the second aspect, preferably, the ratio of the added amounts of bacterial cellulose, 4-dimethylaminopyridine, triethylamine and 2-bromoisobutyryl bromide is 2g:3g:46mL:34mL.

[0020] In combination with the second aspect, preferably, the ratio of the added amounts of the intermediate product I, 1-vinylimidazole, ligand, catalyst and reducing agent is 50g:1500mL:20g:2.5g:23g.

[0021] In combination with the second aspect, preferably, the mass ratio of the molecular brush-modified bacterial cellulose, the polyethylene oxide substrate and the lithium salt is (2-8):40:13.

[0022] The third aspect of the present application provides the use of the reactive solid polymer electrolyte prepared by the preparation method described in the second aspect in a lithium metal battery.

[0023] Compared with the prior art, the advantages or beneficial effects of the embodiments of the present application include at least:

[0024] The reactive solid polymer electrolyte provided in the present application is prepared by uniformly distributing modified bacterial cellulose and lithium salt on a polyethylene oxide substrate, and the modified bacterial cellulose is a reactive molecular brush formed by grafting alkylated polyvinyl imidazole side chains on the surface of the bacterial cellulose. On the one hand, by designing the molecular structure of bacterial cellulose, the nitrogen cations in the polyvinyl imidazole side chains can fix the anions in the lithium salt, weakening their coordination with lithium ions, promoting the rapid transmission of lithium ions, and thus improving the ionic conductivity of the polymer; on the other hand, the rigid cellulose skeleton gives the solid polymer electrolyte excellent mechanical properties and can inhibit the growth of lithium dendrites; thirdly, redox can occur during the charge and discharge process, forming a stable electrolyte / electrode interface, thereby significantly improving the cycle stability of the lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0026] Figure 1 This is a scanning electron microscope image of the modified bacterial cellulose prepared in the examples of the present application;

[0027] Figure 2 Scanning electron micrographs of 10% BC-g-PVIMI / PEO SPE and PEO SPE prepared in the examples of the present application;

[0028] Among them, (a) 10% BC-g-PVIMI / PEO SPE; (b) PEO SPE;

[0029] Figure 3 XRD spectra of 10% BC-g-PVIMI / PEO SPE and PEO SPE prepared in the examples of the present application;

[0030] Figure 4 The stress-strain curves of 10% BC-g-PVIMI / PEO SPE and PEO SPE prepared in the examples of the present application;

[0031] Figure 5Impedance spectra of 10% BC-g-PVIMI / PEO SPE and PEO SPE prepared in the examples of the present application at 60°C;

[0032] Figure 6 This is a stress-strain curve of 5% BC-g-PVIMI / PEO SPE prepared in an example of the present application;

[0033] Figure 7 This is the impedance spectrum of 5% BC-g-PVIMI / PEO SPE prepared in the example of the present application at 60°C;

[0034] Figure 8 This is a stress-strain curve of 20% BC-g-PVIMI / PEO SPE prepared in an example of the present application;

[0035] Fig. 9 This is the impedance spectrum of 20% BC-g-PVIMI / PEO SPE prepared in the example of the present application at 60°C;

[0036] Fig.10 The stress-strain curve of 10% BC / PEO SPE prepared in the comparative example of the present application;

[0037] Fig.11 The impedance spectrum of 10% BC / PEO SPE prepared in the comparative example of the present application at 60°C;

[0038] Fig.12 The reactive solid polymer electrolyte prepared in the present embodiment is used to make a lithium-lithium symmetric battery at 60°C and 0.1 mAh / cm 2 Voltage-time curve under the following conditions;

[0039] Among them, (a) 10% BC-g-PVMI / PEO SPE was made into a lithium-lithium symmetric battery LiI; (b) 5% BC-g-PVMI / PEOSPE was made into a lithium-lithium symmetric battery LiⅡ; (c) 20% BC-g-PVMI / PEO SPE was made into a lithium-lithium symmetric battery LiⅢ; (d) PEOSPE was made into a lithium-lithium symmetric battery LiⅣ;

[0040] Fig.13 A comparison chart of the cycling performance of lithium metal full batteries made of 10% BC-g-PVIMI / PEO SPE and PEO SPE prepared in the examples of the present application at 60°C and 1C;

[0041] Fig.14 This is the cyclic voltammogram of the 10% BC-g-PVIMI / PEO SPE assembled half-cell prepared in the examples of the present application. DETAILED DESCRIPTION

[0042] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0043] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0044] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0045] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0046] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0047] It should be noted that all raw materials and reagents in the examples of the present application were purchased on the market or prepared according to conventional methods well known to those skilled in the art.

[0048] In a first aspect, an embodiment of the present application provides a reactive solid polymer electrolyte, comprising a polyethylene oxide substrate and modified bacterial cellulose and a lithium salt dispersed on the polyethylene oxide substrate;

[0049] Wherein, the modified bacterial cellulose is a reactive molecular brush formed by grafting alkylated polyvinyl imidazole side chains on the surface of bacterial cellulose;

[0050] The mass ratio of the modified bacterial cellulose to the polyethylene oxide substrate is 5%-20%.

[0051] Among them, on the one hand, through the molecular structure design of bacterial cellulose, the nitrogen cations in the side chains of polyvinyl imidazole can fix the anions in the lithium salt, weaken their coordination with lithium ions, promote the rapid transmission of lithium ions, and thus improve the ionic conductivity of the polymer; on the other hand, it contains a rigid cellulose skeleton, which gives the solid polymer electrolyte excellent mechanical properties and can inhibit the growth of lithium dendrites; thirdly, it can undergo redox during the charge and discharge process to form a stable electrolyte / electrode interface, thereby significantly improving the cycle stability of the lithium battery.

[0052] It should be noted that the lithium salt is preferably one or more of lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide) and lithium difluorooxalate borate. Among them, the nitrogen cation in the side chain of polyvinyl imidazole can fix the anion in the lithium salt, weaken its coordination with lithium ions, promote lithium ion transmission, and thus improve the ionic conductivity of the polymer solid electrolyte.

[0053] The second aspect of the present application provides a method for preparing the reactive solid polymer electrolyte according to the first aspect, the method comprising:

[0054] After dispersing bacterial cellulose in N,N-dimethylformamide, adding 4-dimethylaminopyridine and triethylamine to react, then adding 2-bromoisobutyryl bromide to react, separating and collecting to obtain an intermediate product I;

[0055] The intermediate product I, 1-vinylimidazole, a ligand, a catalyst, and a reducing agent are subjected to polymerization reaction in N,N-dimethylformamide, and then separated and collected to obtain an intermediate product II;

[0056] The intermediate product II is subjected to an alkylation reaction with n-butyl iodide to obtain the modified bacterial cellulose;

[0057] The modified bacterial cellulose, polyethylene oxide and lithium salt are mixed, volatilized to form a film and solidified to obtain the reactive solid polymer electrolyte.

[0058] It should be noted that the aqueous solvent in the cellulose dispersion is replaced with N,N-dimethylformamide, and after centrifugation, it is dispersed in N,N-dimethylformamide, 4-dimethylaminopyridine and triethylamine are added, and 2-bromoisobutyryl bromide is added in an inert atmosphere and an ice-water bath environment. After sealing reaction in an inert atmosphere, ethanol is added for quenching, and after centrifugation and washing, intermediate product I is obtained; intermediate product I is dispersed in N,N-dimethylformamide, 1-vinyl imidazole, ligand, catalyst, and reducing agent are added, and sealed reaction is carried out again in an inert atmosphere. After heating, centrifugation, and washing, intermediate product II is obtained. Intermediate product II is a one-dimensional molecular brush. Intermediate product II is dispersed in N,N-dimethylformamide, iodinated n-butane is added for alkylation reaction, sealed reaction is carried out in an inert atmosphere, and bacterial cellulose modified with molecular brushes is obtained after heating, centrifugation, and washing.

[0059] It should be noted that the molecular brush-modified bacterial cellulose, polyethylene oxide substrate and lithium salt are added to acetonitrile, stirred evenly and then cast on a carrier mold, and then vacuum dried to obtain a reactive solid polymer electrolyte.

[0060] In the embodiment of the present application, the ratio of the amount of bacterial cellulose, 4-dimethylaminopyridine, triethylamine and 2-bromoisobutyryl bromide added is preferably 2g:3g:46mL:34mL. By controlling the amount of each raw material added, the hydroxyl groups on the bacterial cellulose can be converted into bromine-containing initiation sites, thereby forming a macromolecular initiator.

[0061] In the embodiment of the present application, the ligand is preferably one or a combination of N,N,N',N",N"-pentamethyldiethylenetriamine, 2,2-bipyridine and tris(2-picolyl)amine; the catalyst is preferably one or more of cupric bromide, cupric chloride, cuprous bromide and cuprous chloride; the reducing agent is preferably one or more of ascorbic acid, stannous isooctanoate and thiourea dioxide.

[0062] In the embodiment of the present application, the ratio of the added amount of the intermediate product I, 1-vinylimidazole, ligand, catalyst and reducing agent is preferably 50g:1500mL:20g:2.5g:23g. Among them, through the action of these ligands, catalysts and reducing agents, reversible atom transfer radical polymerization can be carried out, and then polyvinyl imidazole side chains can be grafted on bacterial cellulose.

[0063] In the examples of the present application, the mass ratio of the molecular brush-modified bacterial cellulose, the polyethylene oxide substrate and the lithium salt is preferably (2-8):40:13.

[0064] The third aspect of the present application provides the use of the reactive solid polymer electrolyte prepared by the preparation method described in the second aspect in a lithium metal battery. The reactive solid polymer electrolyte has excellent mechanical properties, high ionic conductivity, and can form a stable electrolyte / electrode interface, thereby giving the lithium battery excellent cycle stability.

[0065] The technical solution of the present application will be further described below in conjunction with specific embodiments.

[0066] Example 1

[0067] The preparation method of the A1-reactive solid polymer electrolyte (10% BC-g-PVMI / PEO SPE) provided in this embodiment specifically includes:

[0068] S101: 75 g of a bacterial cellulose aqueous dispersion with a mass fraction of 0.8 wt % was weighed, and washed with DMF by centrifugation at 8000 rpm for 10 min. After repeated centrifugation and washing for six times, the mixture was uniformly dispersed in 150 mL of DMF, and 0.90 g of 4-dimethylaminopyridine and 13.6 mL of triethylamine were added. In a nitrogen atmosphere and an ice bath, 10.3 mL of 2-bromoisobutyryl bromide was added, and the mixture was uniformly mixed, and the mixture was reacted at 25-30° C. for 24 h. After quenching with ethanol, the mixture was first centrifuged at 6000 rpm for 5 min with ethanol; then the mixture was centrifuged at 6000 rpm for 5 min with DMF, and washed until the supernatant was colorless to obtain an intermediate product I.

[0069] S102: 0.20 g of intermediate product I was uniformly dispersed in 10 mL of DMF, and 6 mL of 1-vinylimidazole, 80 μL of N,N,N',N",N"-pentamethyldiethylenetriamine, 10 mg of CuBr2 and 92 mg of ascorbic acid were added in sequence, and reacted at 70°C under a nitrogen atmosphere for 24 h. The mixture was centrifuged at 6000 rpm for 5 min with DMF, and washed by centrifugation 3 times to obtain intermediate product II.

[0070] S103: 0.20 g of intermediate II was uniformly dispersed in 20 mL of DMF, 6.3 mL of n-butane iodide was added, and the mixture was reacted at 70 °C in a nitrogen atmosphere for 24 h, and centrifuged at 6000 rpm for 5 min with ethanol; the mixture was washed by centrifugation 3 times to obtain bacterial cellulose modified with a molecular brush;

[0071] S104: 20 mg of molecular brush-modified bacterial cellulose, 200 mg of polyethylene oxide and 65 mg of lithium bis(trifluoromethylsulfonyl)imide were uniformly dispersed in 8 mL of acetonitrile, and then cast in a polytetrafluoroethylene culture dish. The acetonitrile was evaporated at 40°C, and then vacuum dried at 40°C for 24 h to obtain an A1-reactive solid polymer electrolyte, which was recorded as 10% BC-g-PVMI / PEO SPE.

[0072] Example 2

[0073] This embodiment provides a method for preparing an A2-reactive solid polymer electrolyte (5% BC-g-PVMI / PEO SPE) in which the component ratio, preparation operation and process parameters are basically the same as those in Example 1, except that in this embodiment, 10 mg of molecular brush-modified bacterial cellulose, 200 mg of polyethylene oxide and 65 mg of lithium bis(trifluoromethylsulfonyl)imide are added as raw materials for reaction to obtain an A2-reactive solid polymer electrolyte (5% BC-g-PVMI / PEO SPE).

[0074] Example 3

[0075] This embodiment provides a method for preparing A3-reactive solid polymer electrolyte (20% BC-g-PVMI / PEO SPE), in which the component ratio, preparation operation and process parameters are basically the same as those in Example 1, except that in this embodiment, 40 mg of molecular brush-modified bacterial cellulose, 200 mg of polyethylene oxide and 65 mg of lithium bis(trifluoromethylsulfonyl)imide are added as raw materials for reaction to obtain A3-reactive solid polymer electrolyte (20% BC-g-PVMI / PEO SPE).

[0076] At the same time, in order to verify the comprehensive performance of the reactive solid polymer electrolyte prepared in the above examples, the present application provides the following comparative examples for detailed description.

[0077] Comparative Example 1

[0078] The component ratio, preparation operation and process parameters of the B1-solid polymer electrolyte (PEO SPE) prepared in the embodiment of the present application are basically the same as those in Example 1, except that bacterial cellulose is not added in this embodiment to prepare the B1-solid polymer electrolyte (PEO SPE).

[0079] Comparative Example 2

[0080] The component ratio, preparation operation and process parameters of the B2-solid polymer electrolyte (10% BC / PEO SPE) prepared in the embodiment of the present application are basically the same as those in Example 1, except that pure bacterial cellulose is added in this embodiment, and the bacterial cellulose is not modified to prepare the B2-solid polymer electrolyte (10% BC / PEO SPE).

[0081] The performance test results of the reactive solid polymer electrolytes prepared in the examples and comparative examples of the present application are shown in Table 1.

[0082] Table 1 Comprehensive properties of reactive solid polymer electrolytes

[0083]

[0084] In order to verify the appearance performance of the reactive solid polymer electrolyte prepared in the examples of the present application, the reactive solid polymer electrolyte prepared in the examples was characterized, and the results were as follows: Figure 1 to Figure 2 As shown; among them, Figure 1 This is a scanning electron micrograph of bacterial cellulose modified with molecular brushes; Figure 2 Scanning electron micrographs of 10% BC-g-PVIMI / PEO SPE and PEO SPE.

[0085] according to Figure 1 As we know, bacterial cellulose modified by molecular brushes has the microscopic morphology of a one-dimensional molecular brush and is composed of many fibers overlapped to form a porous structure.

[0086] according to Figure 2 As known, (a) SEM image of 10% BC-g-PVMI / PEO SPE; (b) SEM image of PEO-SPE. Compared with PEO SPE, the grain diameter of 10% BC-g-PVMI / PEO SPE is smaller, and the reactive molecular brushes are relatively evenly distributed in the polyethylene oxide substrate.

[0087] In order to verify the structural properties of the reactive solid polymer electrolyte prepared in the examples of the present application, the reactive solid polymer electrolyte prepared in the examples was characterized, and the results were as follows: Figure 3 to Figure 4 As shown; among them, Figure 3 XRD spectra of 10% BC-g-PVIMI / PEO-SPE and PEO-SPE; Figure 4 The stress-strain curves of 10% BC-g-PVIMI / PEO-SPE and PEO-SPE; Figure 5 Impedance spectra of 10% BC-g-PVIMI / PEO SPE and PEO SPE at 60°C; Figure 6 The stress-strain curve of 5% BC-g-PVIMI / PEO SPE; Figure 7 The impedance spectrum of 5% BC-g-PVIMI / PEO SPE at 60°C; Figure 8 The stress-strain curve of 20% BC-g-PVIMI / PEO SPE; Fig. 9 The impedance spectrum of 20% BC-g-PVIMI / PEO SPE at 60°C.

[0088] according to Figure 3 As known, compared with PEO SPE, the diffraction peak intensity of 10% BC-g-PVMI / PEO SPE is significantly reduced, indicating that the introduction of BC-g-PVMI is beneficial to reduce the crystallinity.

[0089] according to Figure 4 As known, the tensile strength of 10% BC-g-PVMI / PEO SPE is 5.2 MPa, which is significantly higher than the tensile strength of PEO SPE 2.1 MPa, indicating that the reactive solid polymer electrolyte provided in the present application has good mechanical properties.

[0090] according to Figure 5 As we know, according to the calculation formula of formula 1,

[0091]

[0092] Where: σ is the ionic conductivity, L is the electrolyte thickness, S is the steel sheet area, and R is the bulk resistance.

[0093] At 60°C, the ionic conductivity of 10% BC-g-PVMI / PEO SPE is 3.0×10 -4 S / cm, while the ionic conductivity of PEOSPE is only 7.4×10 -5 The reason may be that the presence of nitrogen cations in the side chain PVIMI can fix anions, weaken the cation coordination, and promote lithium ion transport.

[0094] according to Figure 6 As known, the tensile strength of 5% BC-g-PVMI / PEO SPE is 3.9 MPa, which is significantly higher than the tensile strength of PEO SPE 2.1 MPa.

[0095] according to Figure 7 As we know, according to formula 1, at 60°C, the ionic conductivity of 5% BC-g-PVMI / PEO SPE is 1.8×10 -4 S / cm.

[0096] according to Figure 8As known, the tensile strength of 20% BC-g-PVMI / PEO SPE is 6.3 MPa, which is significantly higher than the tensile strength of PEO SPE 2.1 MPa.

[0097] according to Fig. 9 As we know, according to formula 1, at 60°C, the ionic conductivity of 20% BC-g-PVMI / PEO SPE is 2.7×10 -4 S / cm.

[0098] according to Fig.10 As known, the tensile strength of 10% BC / PEO SPE is 4.0 MPa, which is significantly higher than the tensile strength of PEO 2.1 MPa.

[0099] according to Fig.11 As we know, according to formula 1, at 60°C, the ionic conductivity of 10% BC / PEO SPE is 1.1×10 -4 S / cm.

[0100] In view of the good mechanical properties and high ionic conductivity of the above-mentioned reactive solid polymer electrolyte, the reactive solid polymer electrolyte can be used as a solid electrolyte in lithium metal batteries.

[0101] The 10% BC-g-PVMI / PEO SPE prepared in Example 1 was applied to a lithium-lithium symmetrical battery, in which a lithium sheet was used as a negative electrode and a positive electrode, and the 10% BC-g-PVMI / PEO SPE was used as a solid electrolyte. The lithium-lithium symmetrical battery was assembled in a glove box with an argon atmosphere, and the moisture and oxygen content in the glove box was kept below 0.1 ppm. The model of the assembled button battery was CR2032, and it was recorded as a lithium-lithium symmetrical battery LiI.

[0102] The 10% BC-g-PVMI / PEO SPE prepared in Example 1 is applied to a lithium metal full battery, in which a lithium sheet is used as a negative electrode, lithium iron phosphate is used as a positive electrode, and 10% BC-g-PVMI / PEO SPE is used as a solid electrolyte. The lithium iron phosphate pole piece is a mixture of lithium iron phosphate active material, conductive carbon black, polyvinylidene fluoride, polyethylene oxide and lithium bis(trifluoromethanesulfonylimide) in a mass ratio of 60:15:15:8:2, which is scraped onto a carbon-coated aluminum foil to form a film, placed in a 60°C oven for drying, and cut into a 12mm diameter size to obtain a lithium iron phosphate pole piece. The assembled button battery has a model of CR2032, which is recorded as a lithium metal full battery LFPI.

[0103] In order to evaluate the interfacial stability of the solid electrolyte during the cycle, the present application uses the 5% BC-g-PVMI / PEO SPE prepared in Example 2, the 20% BC-g-PVMI / PEO SPE prepared in Example 3, and the PEO SPE prepared in Comparative Example 1 as solid electrolytes, and uses lithium sheets as negative and positive electrodes, and assembles them into lithium-lithium symmetric batteries, which are respectively recorded as lithium-lithium symmetric batteries LiⅡ, lithium-lithium symmetric batteries LiⅢ, and lithium-lithium symmetric batteries LiⅣ. Among them, the lithium-lithium symmetric battery LiI, the lithium-lithium symmetric battery LiⅡ, the lithium-lithium symmetric battery LiⅢ, and the lithium-lithium symmetric battery LiⅣ differ only in the type of solid electrolyte, and the preparation method and other raw material types and amounts are the same.

[0104] In order to evaluate the application potential of solid electrolytes, the present application uses the PEO SPE prepared in Comparative Example 1 as a solid electrolyte, lithium iron phosphate as a positive electrode, and a lithium sheet as a negative electrode to assemble a lithium metal full battery, which is recorded as a lithium metal full battery LFPⅡ.

[0105] This application measures, records and plots the influence of four lithium-lithium symmetric batteries, namely, lithium-lithium symmetric battery LiI, lithium-lithium symmetric battery LiII, lithium-lithium symmetric battery LiIII and lithium-lithium symmetric battery LiIV, at 60°C and 0.1 mA / cm 2 and 0.1mAh / cm 2 The voltage-time curve of the cycle under the conditions is as follows: Fig.12 As shown, (a) is the voltage-time curve of the lithium-lithium symmetric battery LiI, (b) is the voltage-time curve of the lithium-lithium symmetric battery LiⅡ, (c) is the voltage-time curve of the lithium-lithium symmetric battery LiⅢ, and (d) is the voltage-time curve of the lithium-lithium symmetric battery LiⅣ.

[0106] according to Fig.12 It can be seen that compared with the lithium-lithium symmetric batteries assembled with 5% BC-g-PVMI / PEO SPE, 20% BC-g-PVMI / PEO SPE and PEO SPE, the lithium-lithium symmetric battery LiI assembled with 10% BC-g-PVMI / PEO SPE has a smaller overpotential and a longer cycle life, showing a more stable lithium deposition / stripping behavior.

[0107] This application also measures, records and plots the cycle performance comparison chart of two lithium metal full batteries, LFPI and LFPⅡ, at 30°C and 0.5C. Fig.13 shown.

[0108] according to Fig.13It can be seen that compared with the lithium metal full battery assembled with PEO SPE, the lithium metal full battery LFPI assembled with 10% BC-g-PVMI / PEO SPE has a higher discharge specific capacity and exhibits good cycling performance.

[0109] In order to further explore the mechanism of 10% BC-g-PVMI / PEO SPE improving the cycle stability of the battery, the present invention uses lithium sheet as the negative electrode, conductive carbon black and polyvinylidene fluoride mixed slurry as the positive electrode, and 10% BC-g-PVMI / PEO SPE as the electrolyte to assemble a half-cell, and uses an electrochemical workstation to perform cyclic voltammetry tests. Fig.14 shown.

[0110] according to Fig.14 As shown in Figure 2, 10% BC-g-PVIMI / PEO SPE has a redox pair during the charge and discharge process, and I- is oxidized to I3 at 3.18 V. - , 3.68V and 3.84V at I3 - is further oxidized to I2; at 3.59V, I2 is reduced to I3 - , I3 at 3.04V - The above results confirm that BC-g-PVIMI undergoes redox during the charge and discharge process, forming a stable electrolyte / electrode interface, thereby significantly improving the cycle stability of the battery.

[0111] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0112] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions recorded in the aforementioned embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.

Claims

1. A reactive solid polymer electrolyte, characterized in that: It comprises a polyethylene oxide substrate and modified bacterial cellulose and lithium salt dispersed on the polyethylene oxide substrate; Wherein, the modified bacterial cellulose is a reactive molecular brush formed by grafting alkylated polyvinyl imidazole side chains on the surface of bacterial cellulose; The mass ratio of the modified bacterial cellulose to the polyethylene oxide substrate is 5%-20%.

2. The reactive solid polymer electrolyte according to claim 1, characterized in that The lithium salt is one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide and lithium difluorooxalatoborate.

3. A method for preparing a reactive solid polymer electrolyte according to any one of claims 1 to 2, characterized in that: The method comprises: After dispersing bacterial cellulose in N,N-dimethylformamide, adding 4-dimethylaminopyridine and triethylamine to react, then adding 2-bromoisobutyryl bromide to react, separating and collecting to obtain an intermediate product I; The intermediate product I, 1-vinylimidazole, a ligand, a catalyst, and a reducing agent are subjected to polymerization reaction in N,N-dimethylformamide, and then separated and collected to obtain an intermediate product II; The intermediate product II is subjected to an alkylation reaction with n-butyl iodide to obtain the modified bacterial cellulose; The modified bacterial cellulose, polyethylene oxide and lithium salt are mixed and volatilized to form a film, thereby obtaining the reactive solid polymer electrolyte.

4. The method for preparing a reactive solid polymer electrolyte according to claim 3, characterized in that: The ligand is one of N,N,N',N",N"-pentamethyldiethylenetriamine, 2,2-bipyridine and tris(2-pyridylmethyl)amine or a combination thereof.

5. The method for preparing a reactive solid polymer electrolyte according to claim 3, characterized in that: The catalyst is one or more of cupric bromide, cupric chloride, cuprous bromide and cuprous chloride.

6. The method for preparing a reactive solid polymer electrolyte according to claim 3, characterized in that: The reducing agent is one or more of ascorbic acid, stannous isooctanoate and thiourea dioxide.

7. The method for preparing a reactive solid polymer electrolyte according to claim 3, characterized in that: The ratio of the added amounts of the bacterial cellulose, 4-dimethylaminopyridine, triethylamine and 2-bromoisobutyryl bromide is 2 g:3 g:46 mL:34 mL.

8. The method for preparing a reactive solid polymer electrolyte according to claim 3, characterized in that: The ratio of the added amounts of the intermediate product I, 1-vinylimidazole, ligand, catalyst and reducing agent is 50g:1500mL:20g:2.5g:23g.

9. The method for preparing a reactive solid polymer electrolyte according to claim 3, characterized in that: The mass ratio of the molecular brush-modified bacterial cellulose, the polyethylene oxide substrate and the lithium salt is (2-8):40:

13.

10. Use of a reactive solid polymer electrolyte prepared by the preparation method according to any one of claims 3 to 9 in a lithium metal battery.

Citation Information

Patent Citations

  • Polymer solid electrolyte, preparation method thereof and solid-state battery

    CN113471531A

  • Grafted cellulose adsorbent as well as preparation method and application thereof

    CN110918067A

  • Molecular brush polymer film based on cellulose network structure, and preparation method and application thereof

    CN112072173A

  • Brush-like cellulose skeleton-based block polymer, preparation method thereof and application of block polymer as solid electrolyte

    CN115286751A

  • Conductive material and the usage

    US20190270876A1